2018
DOI: 10.1017/s000711451800140x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a home fortification programme with multiple micronutrients on infant and young child development: a cluster-randomised trial in rural Bihar, India

Abstract: Research demonstrates the importance of nutrition for early brain development. Few studies have examined the effectiveness of multiple micronutrient powders (MNP) on child development. This study examined the impacts of home fortification with MNP on motor and mental development, executive function and memory of children living in Bihar. This two-arm cluster-randomised effectiveness trial selected seventy health sub-centres to receive either MNP and nutrition counselling (intervention) or nutrition counselling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The elicited imitation task measures children's declarative memory ( 7 ). Our adaptation of the task comprised 8 items based on previously published versions of this task ( 18–21 ). Each item consisted of a set of toys and a sequence of 2 target actions.…”
Section: Methodsmentioning
confidence: 99%
“…The elicited imitation task measures children's declarative memory ( 7 ). Our adaptation of the task comprised 8 items based on previously published versions of this task ( 18–21 ). Each item consisted of a set of toys and a sequence of 2 target actions.…”
Section: Methodsmentioning
confidence: 99%
“…Both samples were randomly selected using a multistage cluster probability proportional to size design. Seventy health subcentres treated as clusters were selected randomly from a single district in Bihar, India, as part of a home fortification randomized effectiveness trial—clinical trial NCT02593136 (Larson et al, ; Young et al, ). A random subsample of 5,664 children were assessed for haemoglobin and anthropometry from a larger survey listing of children 6–18 months of age residing in randomly selected villages within the assigned health subcentre.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 56 intervention studies, 42 measured growth, 17 measured motor, and 22 measured mental, cognitive, language, or socioemotional development (Table S2, online only; in this table, see Refs. , , , , , and ). No iron supplementation trials meeting our inclusion criteria reported brain imaging or chronic disease outcomes.…”
Section: Resultsmentioning
confidence: 99%